The Death of a Child in a Noble Family: Prince Walter Prosper (1839–1841) and the Funeral Ritual of the House of Schwarzenberg in the Nineteenth Century (Theatrum historiae, 2021)
The funeral rituals and ceremonies of the House of Schwarzenberg were passed from generation to generation from the seventeenth and eighteenth century until the interwar period, and contributed significantly to the identity of the family. This article is focused on the specific case of Prince Walter Prosper (1839–1841), who died at the age of two as a consequence of a severe head injury. The article describes not only the ceremonies and rituals which took place during Prince Walter’s funeral, but also uses them to explain the general course of Schwarzenberg burials. As mentioned above, Prince Walter died tragically and suddenly, which was in sharp contrast with the Schwarzenberg ideal of death. The question of the tragic and sudden death of a child and its impact on the rest of the family and its behaviour is also dealt with in this article. Our research is based on the study of the archival material in the Třeboň State Regional Archive, Department in Český Krumlov, where the archive of the House Schwarzenberg is stored, and on a comparison with the research conducted by other Czech historians, mainly Václav Grubhoffer.
Keywords: Schwarzenberg; Walter Prosper; 19th century; death; funeral; rituals; ceremonies; tomb